The intersection of drug interactions and adverse reactions in contemporary antiretroviral therapy. Issue 6 (November 2021) - Nhean, Salin; Tseng, Alice; Back, David
Abstract : Purpose of review: Advances in antiretroviral therapy (ART) have transformed HIV infection into a chronic and manageable condition. The introduction of potent and more tolerable antiretrovirals (ARVs) with favorable pharmacokinetic profiles has changed the prevalence and nature of drug–drug interactions (DDIs). Here, we review the relevance of DDIs in the era of contemporary ART. Recent findings: Management of DDIs remains an important challenge with modern ART, primarily due to increased polypharmacy in older persons living with HIV. Significant DDIs exist between boosted ARVs or older nonnucleoside reverse transcriptase inhibitors and comedications for chronic comorbidities (e.g., anticoagulants, antiplatelets, statins) or complex conditions (e.g., anticancer agents, immunosuppressants). Newer ARVs such as unboosted integrase inhibitors, doravirine, and fostemsavir have reduced DDI potential, but there are clinically relevant DDIs that warrant consideration. Potential consequences of DDIs include increased toxicity and/or reduced efficacy of ARVs and/or comedications. Management approaches include switching to an ARV with less DDI potential, changing comedications, or altering medication dosage or dosing frequency. Deprescribing strategies can reduce DDIs and polypharmacy, improve adherence, minimize unnecessary adverse effects, and prevent medication-related errors. Summary: Management of DDIs requires close interdisciplinary collaboration from multiple healthcare disciplines (medicine, nursing, pharmacy) across a spectrum of care (community, outpatient, inpatient).